Hypothyroidism – An Underestimated Complication After Hemithyroidectomy: A Preliminary Study Report - Neeraj Aggarwal; Sirshak Dutta; Tanaya Panja; Mainak Dutta; Sanjoy Kumar Ghosh; Ramanuj Sinha (Bengal Journal of Otolaryngology and Head Neck Surgery, 2017)
Introduction